Intrinsic Hormone-Like Molecules and External Root Resorption During Orthodontic Tooth Movement. A Systematic Review and Meta-Analysis in Preclinical in-Vivo Research - Spoerri, Andreas; Koletsi, Despina; Eliades, Theodore (Frontiers in Physiology, 2018)
Background: External root resorption constitutes an adverse effect of orthodontic treatment. The aim of the present meta-analysis was to identify the effect of induced intrinsic/ hormone-like molecules such as prostaglandins, interleukins and others on external root resorption after orthodontic tooth movement in experimental animals Methods: An electronic database search of the literature was performed (Medline via PubMed, EMBASE, LILACS, and Open Gray). Search terms included root resorption, tooth movement and animal type. Risk of bias assessment was made using the SYRCLE guidelines for animal studies and reporting quality was assessed through ARRIVE. Random effects meta-analysis was performed for the outcome root resorption after orthodontic tooth movement. Results: Of the 124 articles initially retrieved, 13 were eligible for inclusion in the systematic review, while only 2 were included in the quantitative synthesis. Five studies investigated the effect of Prostaglandin E2, four studies the effect of Thyroxine, two the effect of Calcium ions (Ca++), while the rest investigated Misoprostol, Interleukin-12 and Interleukin-4. Risk of Bias in all studies was judged to be high overall, while reporting quality was suboptimal. According to the quantitative synthesis, there was no difference in root resorption after orthodontic tooth movement when Prostaglandin E2 coupled with Ca++ was administered in comparison to no substance administration (SMD: 0.48 mm2; 95% CI: −0.22, 1.19; p = 0.18). Conclusions: Overall, there was no evidence to suggest a variation in root resorption when Prostaglandin E2 and Ca++ were administered, while there is an overriding need for further high quality experimental studies to inform available evidence on the effect of intrinsic substances on external root resorption.